The Extent to Which Future Skills are Employed During Teaching from the Viewpoint of Students of Islamic Studies and their Relationship to Students' Attitude towards Future Profession (Journal Of Educational and Psychological Researches, 2022)
The research aims to identify the relationship between employing future skills during teaching from the viewpoint of students of Islamic studies at the Northern Border University, as well as their attitudes towards future professions. The researcher employed the correlational descriptive approach. The tools were a questionnaire for employing future skills, and a scale for the attitude towards the future profession. The two research tools were applied to a random sample of (242) male and female students from the department of Islamic Studies, College of Education and Arts. The findings showed that the total level of employing future skills and their three axes during teaching was average. It was also found that the attitude towards future professions among students was average, with a positive and statistically significant correlation between them. The findings did not reveal statistically significant differences between the averages of responses on the questionnaire and the scale due to the difference in gender or academic year. Finally, the study recommended training faculty members to employ future skills during teaching, and to improve students' future professional orientations.